A study on the purchasing behavior among UiTM Sabah, Kota Kinabalu campus student on handphone / Rozanizah Said - Said, Rozanizah (2006)
A mobile phone is an electronic communication device. Most current mobile phones connect to a cellular network of base stations (cell sites), which is in turn interconnected to the public switched telephone network (PSTN). Prior mobile phones operating without a cellular network (the so called OG generation), such as Mobile Telephone Service, date back to 1946. Until the mid to late 1980s, most mobile phones were sufficiently large that they were permanently installed in vehicles as car phones. In addition to the standard voice function of a telephone, a mobile phone can support many additional services such as SMS for text messaging, packet switching for access to the Internet, and MMS for sending and receiving photos and video. The world's largest mobile phone manufacturers include Alcatel, Audiovox, BenQ Siemens, Dopod, Fujitsu, Kyocera, LG, Motorola, NEC, Nokia, Panasonic (Matsushita Electric), Pantech Curitel, Philips, Sagem, Samsung, Sanyo, Sharp, SK Teletech, Sony Ericsson and Toshiba. The world's largest mobile phone operators include Orange SA and Vodafone.